Serum creatinine as a marker of muscle mass in chronic kidney disease: results of a cross‐sectional study and review of literature. Issue 1 (10th July 2012) - Patel, Sapna S.; Molnar, Miklos Z.; Tayek, John A.; Ix, Joachim H.; Noori, Nazanin; Benner, Deborah; Heymsfield, Steven; Kopple, Joel D.; Kovesdy, Csaba P.; Kalantar-Zadeh, Kamyar
Abstract : Background: Higher muscle mass is associated with better outcomes and longevity in patients with chronic disease states. Imaging studies such as dual‐energy X‐ray absorptiometry (DEXA) are among the gold standard methods for assessing body fat and lean body mass (LBM), approximately half of which is comprised of skeletal muscle mass. Elaborate imaging devices, however, are not commonly available in routine clinical practice and therefore easily accessible and cost‐effective, but reliable muscle mass biomarkers are needed. One such marker is serum creatinine, derived from muscle‐based creatine, which is inexpensive and ubiquitously available, and it can serve as a biomarker of skeletal muscle mass in human subjects. Methods and results: In 118 hemodialysis patients, we found that the 3‐month averaged serum creatinine concentration correlated well with DEXA‐measured LBM. The recent literature regarding serum creatinine as a surrogate of muscle mass is summarized, as is the literature concerning the use of other measures of muscle mass, such as plasma gelsolin and actin, and urinary creatinine excretion. We have also reviewed the role of dietary meat intake in serum creatinine variability along with several biomarkers of dietary meat intake (creatine, carnitine, carnosine, ophidine, anserine, 3‐methyl‐l ‐histidine and 1‐methylhistidine). Conclusion: In summary, none of these biomarkers was studied in CKD patients. We advance the hypothesis that in both health and disease, under steady state, serum creatinine can serve as a reliable muscle mass biomarker if appropriate adjustment for full or residual kidney function and dietary meat intake is undertaken.